2020
DOI: 10.3390/su12156175
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation of Carbon Capture and Utilization Applying the Technology of Mineral Carbonation at Coal-Fired Power Plant

Abstract: Based on the operating data of a 40 tCO2/day (2 megawatt (MW)) class carbon capture and utilization (CCU) pilot plant, the scaled-up 400 tCO2/day (20 MW) class CCU plant at 500 MW power plant was economically analyzed by applying the levelized cost of energy analysis (LCOE) and CO2 avoided cost. This study shows that the LCOE and CO2 avoided cost for 400 tCO2/day class CCU plant of mineral carbonation technology were 26 USD/MWh and 64 USD/tCO2, representing low LCOE and CO2 avoided cost, compared to other carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Further, it was found that the energy penalties of CCUS were 1.3–2.95 times lower than CCS in geological formations. The estimated cost of CCUS was 28.15–64 USD/tCO 2 33 …”
Section: Introductionmentioning
confidence: 99%
“…Further, it was found that the energy penalties of CCUS were 1.3–2.95 times lower than CCS in geological formations. The estimated cost of CCUS was 28.15–64 USD/tCO 2 33 …”
Section: Introductionmentioning
confidence: 99%
“…There is a vast literature using LCOE for technoeconomic analysis of energy technologies. A random selection comprises recent publications on concentrated solar power in Spain [10], utility-scale PV [11], wind power [12], wave energy [13], small wind turbines [14], energy storage and renewable technologies [15,16], carbon capture and utilization [17], power to methane [18], hydrogen [19], and biomass technologies [20]). Comparing renewable and conventional energy technologies, consultancies (e.g., [21]), manufacturers (e.g., [22]) and international institutions (e.g., IRENA [23], IEA [24], and IAEA [25]) also use the indicator for cost assessments.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In other words, CO 2 photoreduction through sunlight may replace the current CCS technique due to the high cost of the latter, which vary between the 24 and 47 USD/tCO 2 just for the separation, while it has to be added to the cost for compression (10-13 USD/tCO 2 ) and transportation (extremely dependent on site location) [10]. In addition, it has been reported that a typical CCS facility installed in series to an energy production plant consumes about 0.8 MW/day when the rated capacity is 40 tCO 2 /day [9], thus it is clear that CCS cannot be a long term solution to prevent the annual CO 2 emission, which amounted to about 30 Gton in 2014 [47]. Thus, even if the stage of development of CO 2 photoreduction is too immature for a complete and reliable business model, it is clear that a cost effective and efficient valorization of CO 2 into regenerated fuels or chemicals is compulsory to sustain the virtuous pathway towards a reduction of carbon emissions.…”
Section: Kg Catmentioning
confidence: 99%
“…Energies 2021, 14, 2804 2 of 14 Despite many efforts to dispose of carbon dioxide in alternative ways, such as Carbon Capture and Sequestration (CCS), one of the most promising approaches to reduce the rate of CO 2 emissions is to convert it into regenerated chemicals [7][8][9][10]. As a reagent, carbon dioxide is too stable to react spontaneously under mild conditions (i.e., low temperature and low pressure), but catalyzed reactions and electrochemical processes proved to be effective for the production of methanol, methane, formaldehyde, formic acid and carbon monoxide [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%